1861 : the lost peace - Winik, Jay, 1957- (Grand Central Publishing, 2025)
"1861: The Lost Peace is the story of President Lincoln's far-reaching, difficult, and most courageous decision, a time when the country wrestled with deep moral questions of epic proportions. Through Jay Winik's singular reporting and storytelling, readers will learn about the extraordinary Washington Peace Conference at the Willard Hotel to avert cataclysmic war. They will observe the irascible and farsighted Senator JJ Crittenden, the tireless moderate seeking a middle way to peace. Lincoln himself called Crittenden "a great man" even as Lincoln jousted with him. They'll be inside and among Lincoln's cabinet--the finest in history--which rivaled the executive in its authority, a fact too often forgotten, and they will see a parade of statesmen frenetically grasping for peace rather than the spectacle of the young nation slowly choking in its own blood. A perfect read for history buffs, with timely overtones to our current political climate"--